Instagram PEMANFAATAN AKUN INSTAGRAM @GOARESI SEBAGAI MEDIA INFORMASI WISATA ALAM GOA RESI KECAMATAN BULUKERTO WONOGIRI - Unami Anggraini, Ganis; Suryo, Herning; Mahar R, Fikriana (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
Instagram is a social media platform based on uploading informative photos and videos. The Instagram account @goaresi is an Instagram account that uploads informational content about the Goa Resi tourist attraction. Where the content managed contains information about the Goa Resi tourist attraction. As of June 20, the Instagram account @goaresi has had 3000 followers. The aim of this research is to describe the use of Instagram @goaresi as a tourist information medium for Goa Resi Wonogiri. This type of research is descriptive qualitative research. The technique for determining informants in this research is using purposive sampling technique, data collection techniques using interview and documentation techniques, while for data validity the author uses data triangulation techniques. The data analysis technique uses interactive analysis. Based on the research results, it was concluded that, in using Instagram as an information medium, the @goaresi admin produces content that describes the Goa Resi tourist attraction in the form of photos and videos. The content that has been produced is then uploaded using Instagram features, namely Feeds, Reels, Highlights and Stories. Keywords: Instagram, Goa Resi, information media, tourism